Evaluación de las tendencias de la contaminación del recurso hídrico de la parte media de la microcuenca del Río Cutuchi, en la provincia de Cotopaxi, periodo 2019-2020. - Castro Veloz, Eddytha Judith (2020)
River pollution is a problem that has increased over the years which seriously affects the aquatic biodiversity and productive development of the area. That is why this research was carried out, which objective was to evaluate the trend of the quality of the water resource in the middle part of the Cutuchi river micro watersheds. Data from Fundación Natura and INHAMI-SENAGUA were used for a period of four years (2010-2013). The water quality was evaluated using the CCME and NSF quality indices, and the water quality trends by means of the non-parametric Spearman's Rho test. The results showed that the parameters pH (6.99), total dissolved solids (532.5 mg / l), biochemical demand (28.12mg / l), dissolved oxygen (26.74%) and fecal coliforms (1421.93 NMP / 100ml) are found outside the maximum permissible limits established in the TULSMA for irrigation water and / or for human consumption. The annual average water quality analysis by the ICA NSF method determined that the first three points were of medium quality and the remaining five points of poor quality. By the ICA CCME method it was regular for point 3, marginal for points 1, 2, 4, 5, 6 and 8. However, this method determined point 7 as poor. In the trend analysis, it was observed that point 4 located in the Loreto sector shows a slight improvement that goes from bad to good.